EUFOREA summit in Brussels 2023: inspiring the future of allergy & respiratory care - Hellings, P. W.; Lau, S.; Scadding, G. K.; Bjermer, L.; Backer, V.; Chaker, A. M.; Conti, D. M.; De Corso, E.; Diamant, Z.; Djukanovic, R.; Fokkens, W.; Gevaert, P.; et al. (Frontiers in Allergy, 2023)
In March 2023, the European Forum for Research and Education in Allergy and Airways diseases (EUFOREA) organized its bi-annual Summit in Brussels with expert panel members of EUFOREA, representatives of the EUFOREA patient advisory board, and the EUFOREA board and management teams. Its aim was to define the research, educational and advocacy initiatives to be developed by EUFOREA over the next 2 years until the 10th anniversary in 2025. EUFOREA is an international non-for-profit organization forming an alliance of all stakeholders dedicated to reducing the prevalence and burden of chronic allergic and respiratory diseases via research, education, and advocacy. Based on its medical scientific core competency, EUFOREA offers an evidence-supported platform to introduce innovation and education in healthcare leading to optimal patient care, bridging the gap between latest scientific evidence and daily practice. Aligned with the mission of improving health care, the expert panels of asthma, allergic rhinitis (AR), chronic rhinosinusitis (CRS) & European Position Paper on Rhinosinusitis and Nasal Polyps (EPOS), allergen immunotherapy (AIT) and paediatrics have proposed and elaborated a variety of activities that correspond to major unmet needs in the allergy and respiratory field. The current report provides a concise overview of the achievements, ambitions, and action plan of EUFOREA for the future, allowing all stakeholders in the allergy and respiratory field to be up-dated and inspired to join forces in Europe and beyond.